Sistem Bunyi dalam Bahasa Arab: Sebuah Tinjauan Fonetik dan Fonologis - Teguh Wahyu (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2026)
Arabic is one of the languages that has a complex sound system. The sound system of Arabic consists of three vowel letters and twenty-eight consonant letters. These letters are used to create beautiful and meaningful Arabic words and phrases. The method used in this research is a qualitative approach with a case study methodology. To gain insights into linguistic conflicts in Papua, the research was conducted through language observation, in-depth interviews, and document analysis. It plays a very important role in its phonetic system. Consonants in Arabic are distinguished based on their place and manner of articulation, while vowels can significantly alter the meaning of words. The research findings indicate that learning to write kanji requires significant time and effort, but it can provide valuable benefits in understanding Japanese language and culture.